Improving Student Activities and Learning Outcomes in History Subjects through the Cooperative Integrated Reading and Composition Learning Model - Fitriana, Aprilia Nur (Universitas Negeri Semarang, 2018)
Learning is successful when students can comprehend what has been received. Using learning models not only helps teachers teach but also aids students in understanding the material being studied in greater depth. When effective learning models are employed, they cater to various learning styles, ensuring that students grasp complex concepts more quickly. Results of preliminary observations in High School 2 Magelang provided insightful data, indicating that students of class XI Social 2 still require significant assistance with their activity levels and learning outcomes, particularly in history subjects. The data revealed that the mastery learning level of class XI Social 2 at High School 2 Magelang before the implementation of new strategies was only at 32.5%. This statistic highlights that students' engagement and mastery of the subject matter were alarmingly low, signaling a need for an intervention. This study aimed to determine whether applying the Cooperative Integrated Reading and Composition (CIRC) learning model could increase students' activity and learning outcomes in history courses for class XI Social 2 at High School 2 Magelang during the 2013/2014 school year. The CIRC model promotes cooperative learning, where students work together in small groups, enhancing their reading comprehension and writing skills through integrated activities. By fostering a collaborative learning environment, the CIRC model aims to make learning more interactive and engaging, which can lead to improved academic performance and higher levels of student participation. This research is significant as it explores the potential of innovative teaching methods to address educational challenges and improve student outcomes in a real-world setting.